"Forbidden" Polarisation and Extraordinary Piezoelectric Effect in Organometallic Lead Halide Perovskites. (31st July 2022) - Vasiljevic, Milica; Kollár, Márton; Spirito, David; Riemer, Lukas; Forró, László; Horváth, Endre; Gorfman, Semën; Damjanovic, Dragan
Abstract: Organometallic lead halide perovskites are highly efficient materials for solar cells and other optoelectronic applications due to their high quantum efficiency and exceptional semiconducting properties. A peculiarity of these perovskites is the substantial ionic motion under external forces. Here, it is revealed that electric field‐and light‐induced ionic motion in MAPbX3 crystals (X = Cl, Br, I and MA = CH3 NH3 ) leads to an unexpectedly high piezoelectric‐like response that is at low frequencies an order of magnitude larger than in ferroelectric perovskite oxides. The nominal macroscopic symmetry of the crystals is broken by redistribution of ionic species, which can be controlled deterministically by light and electric field. The revealed piezoelectric response is possibly present in other materials with significant ionic activity, but the unique feature of organometallic perovskites is the strong effect on the piezoelectric‐like response of interplay of ionic motion (MA +1 and X –1 ) and photoelectrons generated with illumination. Abstract : Significant ionic motion can generate extraordinarily high electro‐mechanical coupling in methylammonium lead halide (Cl, Br, I) perovkites. A large piezoelectric effect, which in these materials is sensitive to light, can be induced in nominally centrosymmetric structures (Cl, Br) by an external direct electric field. Such electro‐mechanical coupling mediated by chemical expansion effects should be present in other materials with substantial ionic mobility.